Self-Limited Kleptomania Symptoms as a Side Effect of Duloxetine - Christopher W. T. Miller; Keith E. Gallagher (Case Reports in Psychiatry)
Introduction. Impulse control disorders (ICDs) have been described as a side effect of dopamine agonists, frequently used in neurodegenerative conditions affecting the nigrostriatal pathway. Serotonin-norepinephrine reuptake inhibitors (e.g., duloxetine) have dose-dependent differential affinity for monoaminergic transporters, inhibiting the dopamine transporter at higher doses, thus increasing availability of synaptic dopamine, with the potential for similar impulse control side effects. Case Presentation. A 19-year-old Asian-American female with a history of depression developed new-onset stealing behaviors after an increase in her dose of duloxetine from 60 mg to 90 mg; she described these actions as “compulsive” and irresistible, later experiencing either relief or guilt, features compatible with an ICD. Her symptoms eventually subsided with continued use of 90 mg of duloxetine. Discussion. To the knowledge of the authors, this is the first report of a patient developing new-onset ICD behaviors after being placed on a higher dose of duloxetine, which can inhibit the dopamine transporter and cause difficulty with impulse control. The self-resolving nature of the symptoms may result from compensatory upregulation of dopamine transporters, increasing reuptake of dopamine. Asian populations may be at a higher risk due to the frequent occurrence of CYP2D6 polymorphisms, which decrease the conversion of duloxetine to its inactive metabolites.